Non-avoidance behaviour in enchytraeids to boric acid is related to the GABAergic mechanism - Bicho, Rita C.
Soil invertebrates, e.g. enchytraeids, are known to be able to avoid unfavourable conditions, which gives them an important ecological advantage. These organisms possess chemoreceptors that can detect stressors, which in turn activate responses such as avoidance behaviour. We studied the avoidance behaviour in response to boric acid (BA) using enchytraeids. Results showed not only no avoidance, but that increasing concentrations seemed to have an “attraction” effect. To study the underlying mechanism, a selection of genes targeting for neurotransmission pathways (acetylcholinesterase (AChE) and gamma-aminobutyric acid receptor (GABAr)) were quantified via quantitative real-time polymerase chain reaction (qPCR). Evidences were that BA is neurotoxic via the GABAergic system mechanism where it acts as a GABA-associated protein receptor (GABAAR) antagonist possibly causing anaesthetic effects. This is the first time that (non)avoidance behaviour in invertebrates was studied in relation with the GABAergic system.We strongly recommend the combination of such gene and/or functional assay studies with the avoidance behaviour test as it can bring many advantages and important interpretation lines for ecotoxicity with minor effort.